Comparative Study on the Efficacy and Safety of Tumor Resection in Vitrectomy for Retinal Vasoproliferative Tumors - Bin Zheng; Yan Chen; Lifeng Chen; Huan Chen; Jingwei Zheng; Feng Chen; Zongming Song; Lin Fu; Xuting Hu; Jiandong Pan; Hengli Lian; Lijun Shen; et al. (Journal of Ophthalmology)
Purpose. To investigate the efficacy and safety of combined vitrectomy with tumor resection in the treatment of retinal vasoproliferative tumors (RVPT). Methods. Retrospective study. RVPT patients who underwent vitreous surgery at the Eye Hospital of Wenzhou Medical University from January 2011 to July 2017 were included. The main outcomes included treatment type, tumor activity, and best-corrected visual acuity (BCVA). Results. Altogether, 16 patients with 17 eyes were enrolled with follow-up of no less than 6 months. Eight eyes were in the resection treatment group (Group R) and 9 eyes were in the conservative treatment group (Group C). Female (69%) were more common. The mean age was 50 (49.72 ± 12.92) years. Fifteen patients got unilateral onset and only one patient suffered bilaterally. The common symptoms were decreased visual acuity, floaters, and visual distortion. The preoperative BCVA ranged from hand movement to 20/20, with an average of 0.82 ± 0.75 LogMAR. Patients were all not high myopia, with a mean axial length of 23.27 ± 0.27 mm (21.61 mm to 24.67 mm). Of the retinal diseases, the epiretinal membrane was the most common, followed by vitreous hemorrhage, uveitis, subretinal fluid, and so on. Compared with the baseline BCVA, it improved more at postoperative 6 months and the last visit in Group R than in Group C (P=0.006 and P=0.033). The BCVA-improved 0.2 LogMAR or above in 6 months was 2 eyes in Group C and 7 eyes in Group R. All tumors in Group R were completely resected, whereas three in Group C (33.3%) had definite activity (P=0.008). In all samples, tumors were located on the inner side of the retina and had small vessel wall thickening and hyaline degeneration. The degree of astrocyte proliferation varies widely among different tumors. Conclusions. RVPT was more likely to occur in nonhigh myopia patients. Epiretinal membrane and vitreous hemorrhage were the main causes for vitreous surgery in RVPT patients. Compared with conservative treatment, surgical resection of the tumor is more beneficial to patients on visual acuity recovery and preventing tumor relapse. It is a safe and effective way to treat RVPT.